2017
DOI: 10.1016/j.apergo.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing crowdsourced ratings of speech-based take-over requests for automated driving

Abstract: Take-over requests in automated driving should fit the urgency of the traffic situation. The robustness of various published research findings on the valuations of speech-based warning messages is unclear. This research aimed to establish how people value speech-based take-over requests as a function of speech rate, background noise, spoken phrase, and speaker's gender and emotional tone. By means of crowdsourcing, 2669 participants from 95 countries listened to a random 10 out of 140 take-over requests, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 70 publications
(73 reference statements)
0
14
0
Order By: Relevance
“…For example, only one male voice and one female voice were provided, which means that results may be contingent on the voice generator, accent, pitch, etc. (for a similar discussion on TORs see Bazilinskyy & De Winter, 2017, in which participants rated a number of male and female voices). Also the five traffic situations are merely a selection of possible scenarios in actual automated driving.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…For example, only one male voice and one female voice were provided, which means that results may be contingent on the voice generator, accent, pitch, etc. (for a similar discussion on TORs see Bazilinskyy & De Winter, 2017, in which participants rated a number of male and female voices). Also the five traffic situations are merely a selection of possible scenarios in actual automated driving.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…Both the ISO standard and SAE reports reject the use of the term "take-over" (or "takeover") to address the whole transition process. On the contrary, in literature, it has been found that the term "take-over" has been used to identify the whole transition requiring a TOR (Gonçalves et al 2015;Schwalk et al 2015;Bahram et al 2015;Melcher et al 2015;Zeeb et al 2016;Van Den Beukel et al 2016;Wright et al 2016;Körber et al 2016;Petermeijer et al 2017;Bazilinskyy and De Winter 2017;Borojeni et al 2017b;Forster et al 2017;Zeeb et al 2017;Madigan et al 2018;Van Dintel 2019;Zhang et al 2019;Clark et al 2019;Kraus et al 2020), as inherited from Gold et al (2013).…”
Section: What Does All This Leave Us With?mentioning
confidence: 99%
“…People are more likely to accept takeover requests issued by the multi-modal interface because the multi-modal interface allows the driver to respond more quickly 31 . Bazilinsky et al 32 found that drivers have the highest preference for warning interfaces that include all three modalities (auditory, tactile, and visual). The current research conclusions on multimodal takeover interface are not uniform, and there is a lack of research on trains.…”
Section: Level 3 Highmentioning
confidence: 99%